LEVEL OF CHROMOSOMAL ABERRATIONS, ACTIVE RIBOSOMAL GENES DOSE AND POLYMORPHISM OF DNA REPAIR GENES IN MINERS OF THE KEMEROVO REGION - Тимофеева, Анна Александровна; Минина, Варвара Ивановна; Соболева, Ольга Александровна; Рыжкова, Анастасия Владимировна; Савченко, Яна Александровна; Баканова, Марина Леонидовна; Головина, Татьяна Александровна; Глушков, Андрей Николаевич (Medicine in Kuzbass, 2018)
Objective. Study of the effects of production the environment factors on the miner genome, depending on the variants of the DNA repair genes XRCC2, XRCC3, and the individual dose active ribosomal genes clusters (AcRG). Methods. The level of DNA damage was assessed using the method of accounting of chromosomal aberrations in short-term cultures of blood lymphocytes in 338 workers of Kuzbass coal mines and 480 men of the control group. Using Real-Time PCR, the analysis of the gene XRCC2 (rs3218536) and XRCC3 (rs861539) was carried out. The dose of ribosomal genes active clusters was studied using Ag-coloring chromosome by the method of Howell and Black. Results. A statistically significant (p = 0.0001) increase of the level of chromosomal aberrations in miners was found in comparison with the control group. Miners with an average dose of active ribosomal genes have a statistically significant increase of single fragments incidence (p = 0.038). Increased frequency of chromosome exchanges in workers with a minor T-allele of XRCC3 gene, and in holders of heterozygous GA genotype of XRCC2 with a low dose of active ribosomal genes. Conclusions. These results are important in assessing of the negative effects on the human in populations with similar environmental and production factors. The obtained data of chromosomal aberrations associations, different variants of DNA repair genes, and active ribosomal genes dose are expedient for use in preventive medicine in the formation of high-risk groups. Working at coal cycle enterprises is associated with an increase in the frequency of occurrence of structural chromosome disorders. The association of the polymorphism of the DNA repair genes XRCC2 (rs3218536) and XRCC3 (rs 861539) and the dose of AcRG with an increased risk of chromosomal instability is established.